PERLINDUNGAN HUKUM TERHADAP PEMODAL DALAM PERDAGANGAN SAHAM DAN OBLIGASI DI PASAR MODAL - gede iriana (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2017)
Abstract The capital market is a meeting between the parties that have surplus funds and those who need the funds by way of trade in securities. The title of this research is “Legal Protection to Investor in Trading of Stocks and Bonds in the Capital Market. Problems raised in this study are: How is the regulation of the stocks and bond transactions in the Capital Market?, and How is legal protection for investors in trading of stocks and bonds in the Capital Market?. In this study used normative legal research with approach to legislation, the concept approach, approach to the history and philosophy of law approach, analysis of data using the normative method. Based on this result, it was found that Law Number 8 of 1995 current has arranged the matter that is very important in the Capital Market, namely Parties liability in the Public Offering to meet the principles of transparency, especially the provisions put in order the general public protection. This Law also regulates the liabilities coverage the Parties relating to the Public Offering as Underwriter, Accountant, Legal Consultant, Notary, Appraisers, and other professions, to comply with the liabilities that they must filled, accompanied by threats of indemnity sanctions or criminal sanctions on failure to comply with liabilities under this Law. Protection for investors in the Capital Market Law implemented in two ways namely transparency of information and manipulation prohibition rules. In facts, the protection of information disclosure alone is not sufficient. The various parties involved in the Capital Market possibility doing a disservice to investors, both fraudulent transactions or information deception and trading crime. Legal protection to investors is providing legal certainty through legislation and enforcement. The forms of legal protection such as a preventive action through the stock exchange transaction monitoring continuously to avoid unfair transactions Keywords: Capital Market, Bond, Investors